Case Report: Crown Resorption in a Patient With Junctional Epidermolysis Bullosa and Amelogenesis Imperfecta With LAMB3 Gene Mutations - Urzúa, Blanca; Krämer, Susanne; Morales-Bozo, Irene; Camacho, Claudia; Yubero, María Joao; Palisson, Francis; Fuentes, Ignacia; Ortega-Pinto, Ana (Frontiers in Dental Medicine, 2021)
Background: Epidermolysis bullosa (EB) corresponds to a series of conditions characterized by extreme fragility of the skin and/or mucous membranes. Of the four main types of EB, junctional EB (JEB) is the most associated with alterations in the teeth. The purposes of this study were to determine the clinical, histopathological and ultrastructural characteristics of teeth with amelogenesis imperfecta (AI) in a patient with JEB, to compare them with control teeth and to correlate the findings with the mutations present in the patient. Case report: The study was conducted on a 10-year-old patient with JEB carring two recessive mutations in the LAMB3 gene and the absence of the laminin-332 protein (LM-332), determined by immunofluorescence on a skin biopsy. The patient presents hypoplastic amelogenesis imperfecta with very thin and yellow-brown colored enamel. required eExtractionodontia of two permanent molars were performed due to pain and soft tissue over the crown, compatible resembling with pulp polyp or hyperplastic gingiva. The molars were studied by Light and scanning electron microscopy (SEM) revealed very thing enamel varying from complete absence to 60 microns, absence of normal prismatic structure and presence of a cross-banding with a laminated appearance. The studied teeth had very thin and yellow-brown colored enamel. The histopathological study revealed soft tissue on the crown corresponded to granulation tissue causing generating external crown tooth resorption. With both light and electron microscopy, bands semi-parallel to the dentino-enamel junction were observed in the enamel and absence of prismatic structure. Conclusion: Although coronary resorption has been reported in patients with syndromic and non-syndromic amelogenesis imperfecta, this is the first clinicopathological report of coronary resorption in partially erupted teeth in patients with JEB with mutations in the LAMB3 gene and hypoplastic amelogenesis imperfecta. In patients with this condition, the presence of partially erupted teeth with soft tissue covering part of the crown, without a periodontal pocket and with a radiographic image of abrupt loss of partial coronal radiolucency should lead to suspicion of external coronary resorption.